PENGARUH WEBSITE DESIGN QUALITY DAN KUALITAS JASA TERHADAP REPURCHASE INTENTION : VARIABEL TRUST SEBAGAI VARIABEL MEDIASI - Nicholas Wilson; Keni Keni (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This research was conducted in order to assess the direct and indirect effect of website design quality and service quality toward consumers’ repurchase intention, both directly and indirectly through trust in the Indonesian e-commerce industry. This research implemented survey method, in which questionnaire were distributed to a total of 270 respondents, thus enabling the data to be analyzed. Data were collected from three cities in the Indonesian regions, which are Jakarta, Bandung, and Tangerang. Data were analyzed using partial least squares-structural equation modeling (PLS-SEM) method. Based on the results of the data analysis, it was revealed that both website design quality and service quality had a positive impact on Indonesian consumers’ repurchase intention, both directly or indirectly. Furthermore, trust partially mediated the impact between website design quality, service quality, and repurchase intention.